Four Essays on Technology Licensing and Firm Innovation - Solon Moreira (Copenhagen Business School (CBS), 2014)
Licensing contracts represent one of the most widely used mechanisms to exchange technologies and transfer know-how between firms. Due to the opportunities that licensing creates for firms operating on both sides of the markets for technology, it has increasingly become an integral part of firms' R&D strategies. On the supply side, the existing literature has been focused on understanding how technology licensing can be used by firms as a mechanism to recover investments in innovative activities and to foster learning opportunities. On the demand side, it has been shown that licensing is an important source that firms can tap into to feed their internal needs for innovative knowledge. While several studies have examined technology licensing through the lens of the licensor, research on how firms rely on licensing contracts to acquire knowledge and improve their innovation performance still leaves much to be investigated. Furthermore, with few exceptions, neither organizational nor contractual characteristics related to the licensing deals have received enough attention as determinants of the capacity of the acquiring firm to benefit from licensing in a new technology. The purpose of this dissertation is to investigate the relationship between technology licensing and firm innovation, also examining how the characteristics of the acquiring firm and the use of specific contractual clauses affect this main relationship. The papers in this dissertation build on a different set of theoretical perspectives connected to the licensing literature. The dissertation consists of a general introduction, four papers, and a conclusion. Although all the papers build on the same main dataset related to licensing contracts in the global pharmaceutical industry, supplementary information from different data sources was connected to the licensing contracts to answer the specific research questions. Indeed, each paper, from a different perspective, contemplates and contributes to the existing literature by examining the relationship between technology licensing and specific dimensions of firm innovation. Understanding how licensing deals affect the performance of licensees and licensors is critical to understanding how markets for technology function.
hdl:10398/8868
Keywords: 650